2014
DOI: 10.1074/jbc.m113.528232
|View full text |Cite
|
Sign up to set email alerts
|

5-Aminoimidazole-4-carboxamide-1-β-d-ribofuranoside (AICAR) Effect on Glucose Production, but Not Energy Metabolism, Is Independent of Hepatic AMPK in Vivo

Abstract: Background: AMPK is implicated as the mediator of AICAR action on liver metabolism. Results: AICAR suppresses glucose production independent of AMPK. Regulation of mitochondrial function is AMPK-dependent. Conclusion: Nucleotide monophosphates rely on AMPK to regulate energy metabolism but not to suppress glucose production. Significance: Targeted AMPK activation will not lower glucose production in metabolic diseases but could improve hepatic energetics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
69
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(81 citation statements)
references
References 63 publications
11
69
1
Order By: Relevance
“…The activation of AMPK in skeletal muscle improves insulin sensitivity (O'Neill et al, 2014;Kjøbsted et al, 2015), stimulates glucose uptake (Jørgensen et al, 2004) and enhances fat oxidation (O'Neill et al, 2014), while AMPK activation in the liver leads to reductions in gluconeogenesis (Foretz et al, 2005). The effects of AICAR in the liver are likely not solely attributable to AMPK as the AICAR-mediated inhibition of glucose production was intact in liver-specific AMPK knockout mice (Hasenour et al, 2014).…”
Section: Downloaded Frommentioning
confidence: 99%
See 1 more Smart Citation
“…The activation of AMPK in skeletal muscle improves insulin sensitivity (O'Neill et al, 2014;Kjøbsted et al, 2015), stimulates glucose uptake (Jørgensen et al, 2004) and enhances fat oxidation (O'Neill et al, 2014), while AMPK activation in the liver leads to reductions in gluconeogenesis (Foretz et al, 2005). The effects of AICAR in the liver are likely not solely attributable to AMPK as the AICAR-mediated inhibition of glucose production was intact in liver-specific AMPK knockout mice (Hasenour et al, 2014).…”
Section: Downloaded Frommentioning
confidence: 99%
“…AICAR is an adenosine analogue that is phosphorylated and converted into 5-aminoimidazole-4-carboxamide ribonucleoside 5'-monophosphate (ZMP) (Hasenour et al, 2014). Increases in ZMP, similar to AMP, activate the This article has not been copyedited and formatted.…”
Section: Downloaded Frommentioning
confidence: 99%
“…Metformin and AICAR both activate AMPK. Previous work, including experiments in which AMPK activity was genetically ablated, indicate that AMPK is not essential for regulation of HGP, although both drugs activate AMPK 13, 14, 15, 17, 18. In the current study, we used AMPK activation purely as a marker of drug entry into the cell.…”
Section: Resultsmentioning
confidence: 99%
“…Studies using cAMP analogues have shown previously that the T2D drug metformin and 5‐Aminoimidazole‐4‐carboxamide ribonucleoside (AICAR) repress cAMP‐stimulated hepatocyte glucose production (HGP) 13, 14, 15. Inside cells, AICAR is phosphorylated by adenosine kinase to form ZMP, which then mimics AMP to activate AMPK 16.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation